Domestic Tourism and the Domestic Tourist Experience: Complexities, Idiosyncrasies, and Understandings - Christou, Prokopis A.; Pericleous, Katerina (My University, 2023)
Domestic tourism is a crucial socioeconomic factor for destinations, regions, and local communities. Its peculiarity creates unique opportunities, as well as challenges and complexities, in the formulation of the tourist experience. Two studies examine the complexity of the factors involved in formulating the tourist experience in the context of domestic tourism. A fuzzy-set qualitative comparative analysis of data derived from 394 respondents emphasizes first the nexus of quality and social aspects, then the triad of hygiene, cultural, and price issues, and finally the nexus of quality and novelty aspects. The social element, which embraces social interactions with others and quality time with friends, predominates in forming a posi-tive overall domestic experience, according to an additional qualitative study that delves deeper into the investigated phenomenon by analyzing the responses of forty informants. The findings contribute to the academic milieu of the tourist experience and have direct managerial implications for domestic tourism stakeholders.
Keywords: Tourist experience; Domestic tourism; fsQCA; Fuzzy-set qualitative comparative analysis; Qualitative research